On the rate of rational approximation of functions on tangent continua - Maimeskul, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Upper and lower bounds are established for the rate of rational approximation of functions piecewise analytic on tangent continua. In some special cases, these bounds are coordinated depending on the mutual location of the continua.